Menyingkap Miskonsepsi Gaya dan Gerak: Studi Kasus pada Mahasiswa Pendidikan Fisika FKIP Universitas Mataram dan Rekomendasi Perbaikan - Arsi, Wahyudi; Ayub, Syahrial; Zuhdi, Muhammad (Mataram University, 2025)
The concepts of force and motion constitute a fundamental foundation in classical physics and underpin the understanding of other physics concepts. However, numerous studies indicate that these topics often give rise to persistent misconceptions, including among pre-service physics teachers. This study aims to identify the misconception profiles of Physics Education students at the Faculty of Teacher Training and Education (FKIP), University of Mataram, in 2024 regarding force and motion concepts; to analyze the types and levels of misconceptions; and to formulate recommendations for improving instructional practices. A descriptive quantitative method with a case study approach was employed, utilizing a reasoned multiple-choice diagnostic test as the research instrument. The sample consisted of 25 students enrolled in the Secondary School Physics Studies course. The results reveal a high level of misconceptions, with 24% classified as low, 44% moderate, and 32% high. The most dominant misconceptions were found in the concepts of action–reaction (30%), normal force (27%), and dynamics (25%), while the lowest misconception rate occurred in the definition of force (8%). These findings indicate that the majority of students still experience difficulties in understanding the relationship between force and motion in accordance with Newton’s laws. Furthermore, the analysis shows a negative correlation between the level of misconceptions and academic achievement in advanced physics topics such as work and energy. Based on these results, this study recommends the routine implementation of diagnostic tests, the application of cognitive conflict–based instructional strategies, and the development of innovative teaching materials emphasizing conceptual change to reduce misconceptions and enhance the quality of future physics educators.